(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2023)
Coevolutionary arms races between predators and prey generate some of the most dynamic and ecologically consequential evolutionary interactions in nature, producing phenotypic escalation in defensive and offensive traits that reciprocally drive morphological, physiological, and behavioural divergence on ecological and evolutionary timescales. This study integrated quantitative genetic analysis, population-level genomic data, and long-term field monitoring to characterise coevolutionary dynamics in four predator-prey systems in European mountain ecosystems: golden eagle (Aquila chrysaetos) – mountain hare (Lepus timidus), Eurasian lynx (Lynx lynx) – roe deer (Capreolus capreolus), pine marten (Martes martes) – red squirrel (Sciurus vulgaris), and peregrine falcon (Falco peregrinus) – rock dove (Columba livia). For each system, we quantified: (i) trait covariation between predator attack efficiency and prey evasion capacity (n = 284 individuals per species; morphometric + kinematic analysis); (ii) genomic signatures of coevolutionary selection at candidate loci (n = 84 individuals per species; RADseq; 18,484 SNPs); and (iii) 15-year population dynamics showing predator-prey density oscillations (annual census data 2008–2022). Quantitative genetic analysis confirmed significant heritable variation in evasion traits across all four prey species (mean h2 = 0.42 ± 0.08), and in attack-efficiency traits in predators (mean h2 = 0.38 ± 0.10). RADseq FST outlier analysis identified candidate coevolutionary loci enriched for locomotion, sensory perception, and anti-predator behaviour pathways (enrichment 5.8x above genome background; p < 0.001). Population dynamics showed density-dependent predator-prey cycles with mean period 8.4 ± 1.6 years, consistent with delayed-density-dependence models. These results confirm active coevolutionary dynamics in European mountain predator-prey systems and provide a multimethod framework for quantifying coevolutionary processes in conservation-relevant species assemblages.